2022
DOI: 10.3390/met12061056
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Extraction for Separation of 99.9% Pure Cobalt and Recovery of Li, Ni, Fe, Cu, Al from Spent LIBs

Abstract: In this work, hydrometallurgical recycling of metals from high-cobalt-content spent lithium-ion batteries (LIBs) from laptops was studied using precipitation and solvent extraction as alternative purification processes. Large amounts of cobalt (58% by weight), along with nickel (6.2%), manganese (3.06%) and lithium (6.09%) are present in LiCoO2 and Li2CoMn3O8 as prominent Co-rich phases of the electrode material. The pregnant leach solution (PLS) that was generated by leaching in the presence of 10% H2O2 using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Meshram proposed the extraction equilibria of metals with di-(2-ethylhexyl) phosphoric acid (D2EHPA) and Cyanex 272, as depicted in Figure 3. [81] Previous literature also shows similar equilibria behavior. [82][83][84][85][86] Jian et al, recovered Co and Li elements by adding P507 as an extractant, which contributes to reaching a high Co extraction rate, while the Li extraction rate is very low.…”
Section: Separation and Purification Of Co And LIsupporting
confidence: 55%
See 2 more Smart Citations
“…Meshram proposed the extraction equilibria of metals with di-(2-ethylhexyl) phosphoric acid (D2EHPA) and Cyanex 272, as depicted in Figure 3. [81] Previous literature also shows similar equilibria behavior. [82][83][84][85][86] Jian et al, recovered Co and Li elements by adding P507 as an extractant, which contributes to reaching a high Co extraction rate, while the Li extraction rate is very low.…”
Section: Separation and Purification Of Co And LIsupporting
confidence: 55%
“…Meshram proposed the extraction equilibria of metals with di‐(2‐ethylhexyl) phosphoric acid (D2EHPA) and Cyanex 272, as depicted in Figure 3 [81] . Previous literature also shows similar equilibria behavior [82–86] .…”
Section: Hydrometallurgical Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…15 Literature reports the use of reducing agents such as H 2 O 2 and sodium bisulfite (NaHSO 3 ) to convert Co(III) into Co(II). However, it represents a considerable cost impact in the leaching step as reported by Verma et al 16 Then, separation and purification steps are 17 Precipitation has demonstrated an important technique for Al removal, and the overlap of pH range for different metals makes the attempt of separation for each pure metal ineffective. 17−20 The present study aimed to develop the recycling process of NCA-type Li-ion batteries contributing to the scarce literature regarding this spent battery recycling.…”
Section: Introductionmentioning
confidence: 99%
“…However, it represents a considerable cost impact in the leaching step as reported by Verma et al Then, separation and purification steps are necessary to obtain different products from the leach solution. Solvent extraction has been evaluated, as reported by Meshram et al, using di­(2-ethylhexyl)­phosphoric acid (D2EHPA) and bis-(2,4,4-trimethylpentyl)­phosphinic acid (Cyanex 272) to separate Co from Li, Ni, and Mn after Al precipitation reaching 99% of Co purity . Precipitation has demonstrated an important technique for Al removal, and the overlap of pH range for different metals makes the attempt of separation for each pure metal ineffective. …”
Section: Introductionmentioning
confidence: 99%